Town of Shutehaven, Parish of Conway, County of Herbert - Queensland. Department of Mapping and Surveying (Brisbane : The Dept., 1982)
Cadastral map.
Inset: Diagram [of Shute Harbour]. Scale 1:625.
Keywords: Real property -- Queensland -- Shutehaven -- Maps; Shutehaven (Qld.) -- Maps